Self-Approach Tendencies: Relations With Explicit and Implicit Self-Evaluations - Swinkels, Lieke M. J.; Gramser, Hidde; Becker, Eni S.; Rinck, Mike (Frontiers in Psychology, 2019)
We used a newly developed Self-Approach-Avoidance Task to measure self-approach tendencies in female students. In this task, participants use a joystick to pull portraits of themselves and of others closer or to push them away. In three studies, we found a significant self-approach tendency: Participants were faster to pull mirror-imaged portraits of themselves closer than to push them away. This approach tendency was reduced for non-mirrored self-portraits, and absent for control pictures showing unknown males, unknown females, or empty backgrounds. Moreover, in two out of the three studies, the self-approach tendency was weakly related to explicit self-esteem measured with the Rosenberg Self-Esteem Scale, and in one out of two studies, it was related to implicit self-esteem measured with the Implicit Association Task. Implications and potential applications of the findings are discussed.